1993
DOI: 10.1021/bi00076a023
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A-I conformation in discoidal particles: Evidence for alternate structures

Abstract: To define the conformation of apolipoprotein A-I in discoidal particles, the immunoreactivity of a series of epitopes distributed along the apoA-I sequence has been evaluated in lipid-free apoA-I and in lipid-bound form. To this end, reconstituted discoidal lipoproteins, here called LpA-I, and defined by number of apoA-I per particle (e.g., Lp2A-I), have been prepared with palmitoyloleoylphosphatidylcholine, cholesterol, and apoA-I. Four LpA-I have been obtained and studied: two in the Lp2A-I class, 7.8 and 9.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
84
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(108 citation statements)
references
References 45 publications
24
84
0
Order By: Relevance
“…1), providing mobile regions at either end of helix B (helices 4 and 5), which could potentially act as hinges. Antibody binding studies have identified the 4-5 helix pair as the hinged mobile region (24).…”
Section: Resultsmentioning
confidence: 99%
“…1), providing mobile regions at either end of helix B (helices 4 and 5), which could potentially act as hinges. Antibody binding studies have identified the 4-5 helix pair as the hinged mobile region (24).…”
Section: Resultsmentioning
confidence: 99%
“…The first possibility was that the reduction in particle size reflected a change in the conformation of apoA-I. ApoA-I is a flexible molecule with a hinged domain that may or may not associate with lipid (35,36). If the size of an HDL particle decreases, the hinged region of apoA-I may be removed from contact with lipids.…”
Section: Discussionmentioning
confidence: 99%
“…3), we prepared homogeneous rHDL containing apoA-I and POPC with diameters of 9.6 nm, 12.5 nm, or 17.0 nm containing 2, 3, or 4 apoA-I molecules per particle, respectively, by the cholate dialysis technique (15), as previously described (19).…”
Section: Reconstituted Hdlmentioning
confidence: 99%
“…The incubation time was selected according to the previous results, which showed that the maximal effect in the chymase-dependent inhibition of the cholesterol efflux could be achieved after 2 h of incubation with either chymase. Sequence and molecular mass analyses indicated that band 2 in the SDS-PAGE gel included two distinct polypeptides, with molecular masses of 26 kDa and 25.98 kDa, their N-terminal sequences starting at Asp 1 and Val 19 , respectively (Table 2). Therefore, band 2 contains two polypep- Fig.…”
Section: Identification Of Cleavage Sitesmentioning
confidence: 99%